2020
DOI: 10.3389/fpsyt.2020.00559
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events and Substance Use Disorders in Adolescents

Abstract: Objectives: Adolescents with substance use disorders (SUD) frequently report traumatic events (TEs) and symptoms of post-traumatic stress disorder (PTSD). This study aimed to assess whether lifetime prevalence rates of TEs and PTSD are related to SUD severity in adolescent psychiatric patients. Methods:We analyzed N = 114 self-reports of treatment-seeking German adolescents aged 12 to 18 years, who visited a specialized SUD outpatient unit. Standardized questionnaires were applied to assess SUD severity, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
3
24
0
3
Order By: Relevance
“…Internal consistency of the instrument was large for the present sample (Cronbach's α = 0.84, n = 51 adolescents with complete item data) and in a previous work of our group (Cronbach's α = 0.87, n = 114 adolescent SUD outpatients) [43].…”
Section: Substance Use Disorder Severitysupporting
confidence: 51%
“…Internal consistency of the instrument was large for the present sample (Cronbach's α = 0.84, n = 51 adolescents with complete item data) and in a previous work of our group (Cronbach's α = 0.87, n = 114 adolescent SUD outpatients) [43].…”
Section: Substance Use Disorder Severitysupporting
confidence: 51%
“…Veterans were found to have a higher risk of suffering from many major chronic diseases (i.e., circulatory, nervous, digestive, musculoskeletal, or respiratory diseases) after the war ( 13 ). Studies also shown that adolescents those who experienced stressful events may be worse school performance or have worse health conditions ( 14 ). The subsequent long-term physiological changes, especially inflammatory function disorders, may lead to a decline in overall health and an increase in diseases emergence and even death.…”
Section: Traumatic Stress Disorder May Cause Changes In the Body's Physiological Functionsmentioning
confidence: 99%
“…Furthermore, this study is the first published psychometric assessment of the German version of the DUDIT. While previous studies in German adults (Schäfer et al, 2017;Spencer et al, 2018;Dyba et al, 2019) and German adolescents (Basedow et al, 2020) have used the DUDIT as a measure or screening tool, none have reported on the psychometric properties. Additionally, previous research has assessed the DUDIT on basis of the DSM-IV criteria for substance abuse and dependence (see Hildebrand, 2015 for an overview), which makes this study the first psychometric assessment using the updated DSM-5 criteria with three levels of SUD.…”
Section: Discussionmentioning
confidence: 99%